Comparison of Activated Protein C Resistance With Factor V Leiden Testing by Molecular Assay. (11th September 2019) - Perry, William R; Pipe, Steven W; Li, Shih-Hon
Abstract: Factor V Leiden (FVL) is a variant form of coagulation factor V that is the most common inherited risk factor for venous thromboembolism in people of European ancestry. FVL is associated with the missense mutation, p.R506Q, which encodes a FV protein resistant to cleavage by activated protein C (APC). Laboratory testing for FVL includes both phenotypic assays that assess APC resistance (APCR) and molecular assays that evaluate FVL genotype (FVLM) directly. Although APCR results are typically highly concordant with FVL genotype, discrepancies are known to occur and may result in inference of an incorrect FV genotype if only APCR testing is used. The objective of this study was to compare the results of these two testing methodologies and to identify potential explanations for discrepancies in results. Data were obtained by searching the electronic medical record of a large academic hospital for patients who underwent both APCR and FVLM testing from 2013 to 2018. APCR was evaluated using the ratio between two dilute Russell Viper Venom Time (DRVVT) tests, one preincubated with a protein C activator derived from A contortrix contortrix venom and the other with vehicle; the validated normal APCR ratio is ≥1.7. FVLM was performed by invader analysis utilizing fluorescence resonance energy transfer (FRET). In total, 424 patients underwent testing with both assays. Of 21 patients who had APCR assay clot times that exceeded the measurement range, all were FVLM negative, and 15 were anticoagulated during APCR testing. Of the 403 patients with reportable results for both tests, 385 (95.5%) patients had normal APCR and were FVLM negative. Of the 18 (4.5%) patients with discrepant results, 15 (3.7%) had an abnormally low APCR but were FVLM negative, and 3 (0.8%) had a normal APCR but were FVLM heterozygous. Among the 15 FVLM-negative patients with abnormal APCR <1.7, 11 (73.3%) were on warfarin with/out enoxaparin and had low protein S activity and/or low protein C activity. Of the 3 FVLM heterozygous patients with normal APCR, 1 was on apixaban. Our results demonstrated a high concordance between APCR phenotype and FVLM genotype. The concordance of APCR and FVLM may be limited in patients with low protein S or low protein C activity and those on a range of anticoagulant therapy.